Pelatihan Kader Dalam Upaya Pencegahan Stunting Di Desa Talang Curup - Lorenza, Gracelia Mona; Pramana, Cipta; Fadhilah, Siti (Jurnal Dehasen Mengabdi, 2025)
Stunting in Indonesia is a health issue that continues to receive serious attention from the government. According to data from the Indonesian Nutritional Status Survey (SSGI), the prevalence of stunting in Indonesia has shown a significant downward trend in recent years. The most striking decline occurred between 2021 and 2022, when the prevalence of stunting dropped from 24.4% to 21.6% (Ministry of Health, 2023a). The 2024 Indonesian Health Survey showed that the prevalence of stunting in toddlers aged 0-59 months was 15.8%, while in children aged 0-23 months (toddlers) it was 12.9% (Ministry of Health, 2023b). The government aims to reduce the stunting rate to 14% by the end of 2024, requiring an average reduction of 1.8% to achieve this target (Teja, 2022). The objectives to be achieved through the activity "Training cadres in efforts to prevent stunting in Talang Curup Village" are to increase cadre knowledge about efforts to prevent stunting, Increase cadre awareness about efforts to prevent stunting, Reduce the risk of stunting, improve the quality of life of toddlers, increase cadre participation in improving parenting and eating patterns. In this activity, cadres are given material supplies in the form of counseling, which begins with a pre-test, after which they are given materials, then a question and answer session is carried out which is then to evaluate the cadre's understanding, ending with a post-test. In the pre-test and post-test sessions, cadres are given ten questions with a score of <60 meaning poor knowledge and a score> 60 meaning good knowledge. It is hoped that after participating in this counseling, cadres will be able to maintain and have a high awareness to maintain parenting and nutritional intake in toddlers. Lack of cadre knowledge about efforts to prevent stunting can cause various problems in growth and development and nutrition in toddlers. Stunting is a condition of failure to grow in toddlers due to chronic malnutrition so that children are shorter for their age. (malnutrition occurs since the baby is in the womb and in the early life after birth, but only appears after the child is 2 years old). Understanding of stunting prevention efforts for cadres does not have good knowledge regarding stunting prevention. So with the provision of this education in Talang Curup Village, it is hoped that it can increase the knowledge of cadres and influence behavior in maintaining parenting and eating patterns as well as clean and healthy living. The method used is lectures and group discussions that take place interactively. The number of cadres who attended was 10 people. Cadres really need health education that discusses stunting prevention efforts. The results of this activity achieved the goal, The outreach activity of providing education on stunting prevention efforts to increase the knowledge of cadres in Talang Curup Village has increased the knowledge of cadres so that it is expected to continue to increase the knowledge of cadres about stunting, The achievement of the target in this community service activity which is targeted is cadres with a total of 10 people, The achievement of the target of this community service activity is increasing adolescent knowledge about stunting prevention efforts. This can also be seen from the post-test results which are better than the pre-test results. In the post-test results, it can be seen that most of the cadres who initially had low scores have improved. This is certainly a benchmark that the material presented can be well received by the counseling participants. From the results of this counseling, it can be concluded that the counseling material on "Cadre Training in Stunting Prevention Efforts in Talang Curup Village" is an effective method in increasing cadre knowledge regarding stunting and its prevention, this can also be seen from the results of the post-test and pre-tests which are better than the results of the pre-test. In the post-test results, it can be seen that most of the adolescents who initially had low scores have improved. This is certainly a benchmark that the material presented can be well received by the counseling participants, it is hoped that this increase in knowledge can change the attitude of cadres to be more concerned with stunting prevention.